Bacterial Isolates from Diabetic Foot Ulcer with Antibiotic Sensitivity Pattern - Biswas, Suttam Kumar; Roy, Shilpi Rani; Paul, Arup Roton (Community Based Medical Journal, 2024)
A cross-sectional, descriptive study was carried out in the Department of Surgery, Mymensingh Medical College Hospital, Mymensingh, Bangladesh, between October 2014 and September 2015, to determine the microbiological profile and antibiotic susceptibility patterns of organisms isolated from diabetic foot ulcer. A total of 130 patients of diabetic foot ulcer were included in the study according to inclusion and exclusion criteria. Samples of pus were collected from those patients and sent for culture and sensitivity tests. Out of 130 cases, the highest number of patients 55(42.4%) were in 50-59 years age group. The mean age was 60.1±9.8 years. Most of the patients (70%) were male. 90(69.2%) samples yielded growth, while 40(30.8%) did not show any bacterial growth. Out of those 90 samples with growths, 112 bacteria were isolated. Of them, 59(52.7%) organisms were gram-positive, while 28(25%) were gram-negative and 25(22.3%) organisms were both gram-positive and gram-negative. Out of 59 gram-positive isolates, 35(59.3%) were S. aureus, 18(30.5%) were Enterococci, and 6(10.2%) were Streptococci. In 28 gram-negative isolates, 15(53.7%) were E. coli, 6(21.4%) were Pseudomonas, 4(14.2%) were klebsiella, and 3(10.7%) were proteus. Regarding antibiotic sensitivity, all gram-positive bacteria (100%) were sensitive to vancomycin. S. aureus was 80% sensitive to ceftriaxone, 71.4% to flucloxacillin, 65.7% to clavulanic acid, 54.2% to ampicillin, 48.5% to amoxicillin, and 28.5% to cotrimoxazole. Enterococci spp. was 61.1% sensitive to ceftriaxone, 33.3% to clavulanic acid, (27.7%) to ampicillin, and 16.6% to both amoxicillin and cotrimoxazole. Streptococcus spp. showed 83.3% sensitivity to ceftriaxone, 66.6% to flucloxacillin, 33.3% to clavulanic acid, and 16.6% to cotrimoxazole. Among gram-negative bacteria, E. coli was found to be sensitive to imipenem (100%), ceftriaxone (86%), amikacin (100%), cefuroxime (73.3%), ampicillin (33.3%), ciprofloxacin (60%), and gentamycin (60%). Pseudomonas was found to be sensitive to imipenem (50%), ceftriaxone (66.6%), amikacin (83.3%), and cefuroxime (66.6%). Klebsiella was found to be sensitive to imipenem (100%), ceftriaxone (75%), amikacin (75%), cefuroxime (50%), and ciprofloxacin (25%). Proteus was found to be sensitive to imipenem (100%), ceftriaxone (66.6%), amikacin (66.6%), cefuroxime (33.3%), ciprofloxacin (66.6%), and gentamycin (66.6%). CBMJ 2024 January: vol. 13 no. 01 P: 89-94